JOURNAL OF INTERNATIONAL STUDIES Scientific Papers (2010)
The Journal of International Studies is a quarterly, open access scholarly journal published by Centre of Sociological Research in co-operation with University of Szczecin (Poland), Academy of Economic Studies in Bucharest (Romania) and University Col
lege of Business in Prague (Czech Republic). The journal is dedicated to advancing the socio-economic analyses of societies, institutions, organisations, groups, networks and their interactions. Looking back on 2014 we see the growing of interest i
n JIS. Taking this possibility, we would like to say thank you to all our contributors, researchers and readers. At the present moment, we see the necessity to update our strategies and mission for forthcoming years in order to comply with your needs a
nd expectations. First of all, we became the part of open access process and all materials are available online. Secondly, from 2017 JIS became a quarterly publication.